2006
DOI: 10.1590/s0100-83582006000200010
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da adubação nitrogenada em cobertura sobre a seletividade de herbicidas à cultura do milho

Abstract: O objetivo deste trabalho foi avaliar os efeitos da adubação nitrogenada de cobertura sobre a seletividade dos herbicidas aplicados em pós-emergência na cultura do milho (Zea mays). Para isso, foram conduzidos dois experimentos. Em um deles utilizou-se uréia incorporada (67,5 kg N ha-1) como fonte nitrogenada e, no outro, sulfato de amônio (62 kg N ha¹) a lanço. Os tratamentos foram conseqüência da combinação fatorial entre quatro níveis do fator herbicida: mesotrione (144 g ha-1) + atrazine (1.500 g ha-1), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
4
0
2
Order By: Relevance
“…As for maize crop yield, for both Marechal Cândido Rondon and Entre Rios do Oeste, there were no significant effects in any of the study sources of variation, nor for their interaction (Table 7). Nicolai et al (2006) e Procópio et al (2006) found results similar to those present in maize crops, i.e., the application of mesotrione did not interfere in the development and yield of the crop.…”
supporting
confidence: 70%
“…As for maize crop yield, for both Marechal Cândido Rondon and Entre Rios do Oeste, there were no significant effects in any of the study sources of variation, nor for their interaction (Table 7). Nicolai et al (2006) e Procópio et al (2006) found results similar to those present in maize crops, i.e., the application of mesotrione did not interfere in the development and yield of the crop.…”
supporting
confidence: 70%
“…Currently, for yields above 12 t ha -1 of maize, hybrids with high productive potential have been used and are fertilized with nitrogen doses of up to 240 kg ha -1 (Resende et al, 2012). These N levels are far above the doses tested in several studies on the interaction between herbicides and nitrogen fertilization timing (Nicolai et al, 2006;Guerra et al, 2010;Rodrigues et al, 2012;Souza Jr., 2015). Significant interactions between N fertilization rate and weed control efficiency of herbicides have been observed (Cathcart & Chandler;Swanton, 2004;Sønderskov, Swanton, & Kudsk, 2012).…”
Section: Introductionmentioning
confidence: 82%
“…Many farmers in Midwestern Brazil do not use nicosulfuron because corn is sensitive to it. In addition, nicosulfuron application near to nitrogen fertilizer with fast nitrogen release enhances its phytotoxicity and can reduce plant height and grain yield (Nicolai et al, 2006;Guerra et al, 2010). A recent study on the timing of nitrogen application near nicosulfuron did not show significant effect on corn grain yield (Rodrigues et al, 2012).…”
Section: Introductionmentioning
confidence: 99%